Building Students' Critical Thinking Skills through Authentic Learning by Designing Eco-brick Social Campaigns - Mega Elvianasti; Meitiyani Meitiyani; Maesaroh Maesaroh; Irdalisa Irdalisa; Husnin Nahry Yarza (STAI Hubbulwathan Duri, 2021)
Critical thinking skills are included in the ten skills needed in the era of the industrial revolution 4.0. Students are trained to be able to analyze problems and find solutions from various sources. To enhance the critical thinking skills of students, activities that can be developed are needed, namely through authentic learning, one of which is designing an eco-brick social campaign to overcome plastic waste. Authentic learning activities are in the form of real-world relevance, multiple sources and perspectives, collaboration, reflection, ill-defined problems, and sustained investigation. The quasi-experimental method was used in this study, with the research subjects being 62 students in one of the East Jakarta Junior High Schools in grades 7F and 7H. The data analysis technique in this study was to analyse the results of validity, normality, homogeneity, and independent t-test using SPSS 20 as a statistical tool. According to the research results, it was found that the difference in the average critical thinking ability between groups of students, experiment class with authentic learning treatment revealed 80.73% and control class showed 70.37%. A large number of students have difficulty in critical thinking, namely in the aspect of explaining reasons. Meanwhile, in designing eco-brick social campaigns, the experimental class is in a pretty good category, so it can be revealed that students can build critical thinking skills in solving problems through authentic learning to design eco-brick social campaigns and it is suggested that the different contents in the form of authentic learning in creating social campaigns can be developed.